Rancang Bangun Penyusunan Laporan Keuangan Bagi UMKM Somano Berbasis EFA (Excel For Accounting) - Monarasi, Selfia; Yutanto , Hariadi (WAHANA, 2021)
The object of this research is MSME SOMANO which is one of the MSMEs located in Medokan Ayu, Rungkut District. SOMANO SMEs are engaged in food and beverages made from Pedada fruit (Sonneratia Caseolaris). This study aims to find out how the recording system is carried out by SOMANO SMEs and prepare financial reports using the Microsoft Excel for Accounting (EFA) application. This study uses a descriptive qualitative approach using primary and secondary data. The results of this study indicate that the understanding of SOMANO SMEs regarding SAK-EMKM is still low, and in recording it is assisted by the Trade Office. The design and construction of the preparation of financial statements using Microsoft Excel for Accounting (EFA) was made according to the needs of SOMANO SMEs, this can help and provide positive results for their business, with the preparation of financial statements based on SAK EMKM can be used as a guide in preparing financial statements with using Microsoft Excel for Accounting (EFA).